CHALLENGES OF FOOD SECURITY (Conferencea, 2022)
Food security implies that people may consume the ingredients they need for an active and healthy lifestyle at any time, in any quantity or variety. As a result, it should be mentioned that in the process of globalization, it has become vital to provide high-quality, low-cost food to the country's population. Food is one of the most important factors in human survival. Customers seek high-quality, risk-free products. We commonly define "safe food" as high-quality, environmentally friendly, devoid of GMOs (genetically modified organisms), and free of potentially harmful food-related variables such as pesticides. This article examines the current food security issues.